The business [ (Channel 4, 2004)
Profiles two dynamic business - an established chain of sushi restaurants and a small independent record label - across six precarious months of operation. The programmes demostrate the distinct processes that they undertake to meet the needs of their customers and stay afloat and shows the gritty reality of the enterprise environment today as the companies work to survive.